Mindfulness untuk Peningkatan Subjective well-being : Studi pada Caregiver Lansia - Aurelia Jane; P. Tommy. Y. S. Suyasa (CV. ULIL ALBAB CORP, 2025)
This research is motivated by caregivers' problems in perceiving their life experiences negatively. Elderly caregivers are at risk of experiencing burnout. The measuring instrument used to measure mindfulness is the Mindfulness Attention Awareness Scale (MAAS), while subjective well-being is measured using the Satisfaction with Life Scale (SWLS) and the Positive and Negative Affect Schedule (PANAS). Therefore, efforts need to be made to anticipate and prevent burnout among caregivers. The participants in this study are caregivers aged between 18 and 59 years, with 43 males and 166 females. The results indicate that mindfulness plays a role in predicting subjective well-being. Caregivers can practice mindfulness by learning to be more aware of their presence in the current moment and location. With mindfulness, it is hoped that caregivers can manage stress effectively and enhance their overall subjective well-being. Furthermore, the benefits extend not only to the caregivers themselves but also positively impact the quality of care provided to the elderly. This study recommends integrating mindfulness into training programs for caregivers as a strategic step to improve the well-being of both parties.